Estimates of Glomerular Filtration Rate: comparison of different creatinine based equations - Mohd Hanafiah, Farah Nadia; Md Ralib, Azrina; Abd. Rahim, Mohd. Shahrir (2021)
Objective: Kidney disease is a worldwide health concern with an increasing number of patients and increasing mortality in the past 10 years. The Kidney Disease Improving Global Outcomes (KDIGO) guideline advocates the use of estimated glomerular filtration rate equation (eGFR) to estimate renal function. We evaluated the performance of Cockroft Gault (CG), Modified Diet of Renal Disease (MDRD) and Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equations to measured GFR 99mTc-DTPA considering BMI and age group. Methods: This is a cross sectional study using the existing record of patients that as referred for 99mTc-DTPA scan at the Breast Centre of International Islamic University Malaysia. The record was taken from patients visiting the center from January 2016 to December 2019. The inclusion criteria include age more than 18 years old and not pregnant. Results: A total of 126 patients’ data was collected. All estimated GFR were analyzed in relation to measured GFR by 99m Tc-DTPA scan. The mean measured GFR by 99mTc-DTPA scan was 42.2 + 20.38 ml/min, these was lower than that estimated by CG, MDRD and CKD-EPI equations (53.81 + 36.11, 53.65 + 34.24 and 53.28 + 32.9 ml/min, respectively). CKD-EPI had the highest correlation of 0.72, least bias (mean bias of 11.08 + 23.08) and was more precise (r2 of 0.4) as compared to MDRD and CG. In patients younger than 65 years old, CKD-EPI had the highest correlation however MDRD had the least bias and highest accuracy. In terms of BMI, CKD-EPI had the least bias and highest accuracy for BMI more than 30 and with highest correlation for all classes of BMI. Conclusion: By comparing estimated GFR to measured GFR, CKD-EPI has the best estimation of GFR considering the effect of BMI, age and different stages of chronic kidney disease